Orientation of marine spatial planning in Vietnam - Tran, Duc Thanh; Dang, Hoai Nhon; Nguyen , Van Thao; Cao Thi , Thu Trang; Vu, Duy Vinh; Duong, Thanh Nghi; Nguyen , Dang Ngai (Vietnam Journal of Marine Science and Technology, 2021)
Marine Spatial Planning (MSP) in Vietnam has an ecosystem-based approach. It allocates and designs a balanced and rational marine space for sustainable marine development for economic, social, and ecological purposes. The four primary targets of the MSP are related to socio-economic development, ensuring national defense - security, rights and interests at sea; ecological balance maintenance and environment protection; sustainable marine management. MSP is defined to 2030, with a vision to 2050, based on five viewpoints and ten basic principles. The MSP framework consists of 10 basic activities: Strengthening institutions and policies to create a legal corridor; organizing and enhancing the capacity of management to implement MSP; establishing financial sources and mechanisms for MSP; participation of stakeholders and scientists; establishment of MSP; appraise and approve the MSP; licensing and revocation of licenses to use marine space; harmonize and minimize conflicts of interest in the maritime area use; MSP monitoring and evaluation; MSP adjustment. These activities are arranged in a 5-step cycle. According to MSP, the allocation of marine space is classified into four main groups of use sectors: Marine economic development, conservation, and protection of nature; particular use; reserved area. Depending on the MSP levels, the sectors of marine spatial use can be divided in more detail. MSPs are proposed to be decentralized into three groups: National, regional, and local. Each MSP level has an accompanying planning map at an appropriate scale. Each MSP level has relevant authorities responsible for establishment, submission, approval and implementation.